College student dropout: cohort study about possible causes - Rodríguez-Pineda, Magaly (2021)
The main objective of this research was to find the reasons why first-year students drop out, particularly from Universidad Nacional in Costa Rica. An exploratory, non-experimental and correlational quantitative approach was used. Participants, including 158 students from the 2014 cohort who did not enrollment during the first cycle of 2015, were given a 25 item-questionnaire. Using an exploratory factor analysis, university dropout variables were associated to the following factors (1) academic and student environment, such as grades; (2) motivational, mainly related to mood, length of the program, and lack of orientation, among others; (3) family economic, associated with lack of scholarships, family problems, or change in marital status; and (4) vocational, such as lack of interest and perceiving the program selected as first choice as being of little use. In addition, dropout was higher in stratum 3 students, that is, those from schools with lower educational opportunities and more vulnerable social groups.